Endothelial dysfunction due to the inhibition of the synthesis of nitric oxide: Proposal and characterization of an in vitro cellular model - Silva, Fernanda Cardoso da; Araújo, Bruna Juber de; Cordeiro, Carina Santos; Arruda, Vinícius Marques; Faria, Bruno Quintanilha; Guerra, Joyce Ferreira Da Costa; Araújo, Thaise Gonçalves De; Fürstenau, Cristina Ribas (Frontiers in Physiology, 2022)
The vascular endothelium plays a pivotal role in the maintenance of vascular homeostasis, mediated by vasoactive molecules produced by endothelial cells. The balance between vasoconstrictor and vasodilator biomolecules is what guarantees this equilibrium. Therefore, an increase in the bioavailability of vasoconstrictors along with a reduction in vasodilators may indicate a condition known as endothelial dysfunction. Endothelial dysfunction is marked by an inflammatory process and reduced activity of vasoprotective enzymes, being characterized by some factors like the reduction of the bioavailability of nitric oxide (NO) and increase in the production of reactive oxygen species (ROS), pro-inflammatory and vasoconstrictor molecules. This condition is a predictive marker of several cardiovascular diseases (e.g. atherosclerosis, hypertension, and diabetes). Research is affected by the scarcity of suitable in vitro models that simulate endothelial dysfunction. The goal of this study was to induce an in vitro condition to mimic endothelial dysfunction by inhibiting NO synthesis in cells. Thymus-derived endothelial cells (tEnd.1) were treated with different concentrations of L-NAME (from 1 to 1,000 μM) for different times (12, 24, 48, 72, 96, and 120 hours without and with retreatment every 24 hours). Cell viability, nitrite concentration, p22phox, NOX2, NOX4, IL-6, and ACE genes expression and lipid peroxidation were evaluated. The results indicate that the treatment with 100 μM L-NAME for 72 hours without retreatment reduced NO concentration and NOX4 gene expression while increasing ACE expression, thus mimicking reduced vascular protection and possibly increased vasoconstriction. On the other hand, treatment with 100 μM L-NAME for 96 hours with retreatment reduced the concentration of NO and the expression of the p22phox gene while increasing the expression of the IL-6 and ACE genes, mimicking the increase in inflammation and vasoconstriction parameters. Based on these results, we thus propose that both 100 μM L-NAME for 72 hours without retreatment and 100 μM L-NAME for 96 hours with retreatment may be used as models for in vitro endothelial dysfunction according to the purpose of the study to be conducted.